2021
DOI: 10.1080/21655979.2021.2005932
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The myocardial infarction-associated transcript 2 inhibits lipid accumulation and promotes cholesterol efflux in oxidized low-density lipoprotein-induced THP-1-derived macrophages via inhibiting mitogen-activated protein kinase signaling and activating the nuclear factor erythroid-related factor 2 signaling pathway

Abstract: Dysregulated lipid metabolism of macrophages contributes to thrombosis and antiphospholipid syndrome (APS). The long non-coding RNAs (lncRNA) myocardial infarction-associated transcript 2 (Mirt2) has been reported to inhibit inflammation and lipid accumulation; therefore, this study intended to clarify whether Mirt2 served a role in lipid metabolism. THP-1-derived macrophages with or without Mirt2-knockdown or overexpression, were exposed to oxidized low-density lipoprotein (ox-LDL), then cell migration, lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…ARID5B‐bound regions are predominantly associated with active transcription, 39 and lncRNA dysfunction has been shown to lead to autoimmune disorders and may contribute to APS 6 . Therefore, anti‐ARID5B CUT&Tag was performed using THP‐1 cells to screen downstream lncRNAs involved in APS pathogenesis (Supporting Information S4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…ARID5B‐bound regions are predominantly associated with active transcription, 39 and lncRNA dysfunction has been shown to lead to autoimmune disorders and may contribute to APS 6 . Therefore, anti‐ARID5B CUT&Tag was performed using THP‐1 cells to screen downstream lncRNAs involved in APS pathogenesis (Supporting Information S4).…”
Section: Resultsmentioning
confidence: 99%
“…ARID5B‐bound regions are predominantly associated with active transcription, 39 and lncRNA dysfunction has been shown to lead to autoimmune disorders and may contribute to APS. 6 Therefore, anti‐ARID5B CUT&Tag was performed using THP‐1 cells to screen downstream lncRNAs involved in APS pathogenesis (Supporting Information S4 ). The results validated eight lncRNAs located within upstream 5 kb of the ARID5B's TSS (Figure 2A ), and their transcription might be regulated by ARID5B.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have confirmed the crucial roles of lipid metabolism in early embryo development, implantation, and uterine receptivity [ 26 ]. Meanwhile, dysregulated lipid metabolism is associated with the development and poorer prognosis of APS and thrombosis [ 27 , 28 ]. Our proteomics research has revealed a tight association between plasm exosomes from APS pregnant individuals and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%